2016
DOI: 10.2527/jas.2015-9855
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme supplementation to improve the nutritional value of fibrous feed ingredients in swine diets fed in dry or liquid form1

Abstract: This study evaluated the effect of xylanase supplementation (with or without), feeding method (dry or liquid), and feedstuff (corn distiller's dried grains with solubles [DDGS] or wheat middlings) on apparent total tract digestibility (ATTD) and apparent ileal digestibility (AID) of GE and nutrients, intestinal morphology, ileal and cecal pH, and VFA concentrations. Sixty-four growing pigs (25.87 ± 0.38kg initial BW) were blocked by BW and sex and randomly assigned to 8 dietary treatments. Within each feedstuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 63 publications
8
25
1
1
Order By: Relevance
“…Additionally, the AID of CP, ash, CHO, and GE in the WSM diet was decreased with the inclusion of OCM. Similar results were also found in some previous studies, which found that the exogenous enzyme addition had negative effects on nutrient and energy digestibility in the foregut section [ 13 , 41 ]. However, on the contrary, more studies reported that the exogenous enzymes supplementation could increase the nutrient and energy digestibility for pigs fed wheat and/or wheat by-products diets [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the AID of CP, ash, CHO, and GE in the WSM diet was decreased with the inclusion of OCM. Similar results were also found in some previous studies, which found that the exogenous enzyme addition had negative effects on nutrient and energy digestibility in the foregut section [ 13 , 41 ]. However, on the contrary, more studies reported that the exogenous enzymes supplementation could increase the nutrient and energy digestibility for pigs fed wheat and/or wheat by-products diets [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“… Zeng et al (2018) recently reported that addition of an enzyme blend (galactanase, xylanase, mannanase, α-amylase, and cellulase) improved AID, but not ATTD, of energy, NDF, and nonstarch polysaccharides ( NSP ) constituents in wheat bran containing diets. This indicates that enzyme supplementation may shift fiber degradation from the hindgut to the small intestine, which is supported by Ndou et al (2015) and Moran et al (2016) . Energy absorbed in the small intestine will be used by the pig with greater efficiency than if it is released by fermentation in the lower gut ( Patience, 2017 ).…”
Section: Discussionmentioning
confidence: 73%
“…Однак на 58 добу дослідження співвідношення між вказаним елементами у тварин ІІ-V дослідних груп було в межах 2,0-1,73:1, що свідчить про більш виражений дозозалежний вплив сполук силіцію на метаболізм Фосфору впродовж тривалішого періоду випоювання добавок. З літературних джерел (Marounek et al, 2009;El-Sagheer & Hassanein, 2014;Moran et al, 2016) відомо, що потреба мікрофлори кишечнику в деяких мінеральних елементах може бути вищою за потребу організму тварин. Очевидно сполуки силіцію у фізіологічних кількостях створюють оптимальне середовище для життєдіяльності мікрофлори сліпої та товстої кишок кролів, що сприяє їхньому росту, підвищує ферментативну активність, у результаті чого активується перетравність і засвоюваність корму та мінеральних речовин у травному каналі тварин досліджуваних груп.…”
Section: таблицяunclassified